Metabolic Engineering for Valorization of Agri- and Aqua-Culture Sidestreams for Production of Nitrogenous Compounds by Corynebacterium glutamicum - Wendisch, Volker F.; Nampoothiri, K. Madhavan; Lee, Jin-Ho (Frontiers in Microbiology, 2022)
Corynebacterium glutamicum is used for the million-ton-scale production of amino acids. Valorization of sidestreams from agri- and aqua-culture has focused on the production of biofuels and carboxylic acids. Nitrogen present in various amounts in sidestreams may be valuable for the production of amines, amino acids and other nitrogenous compounds. Metabolic engineering of C. glutamicum for valorization of agri- and aqua-culture sidestreams addresses to bridge this gap. The product portfolio accessible via C. glutamicum fermentation primarily features amino acids and diamines for large-volume markets in addition to various specialty amines. On the one hand, this review covers metabolic engineering of C. glutamicum to efficiently utilize components of various sidestreams. On the other hand, examples of the design and implementation of synthetic pathways not present in native metabolism to produce sought after nitrogenous compounds will be provided. Perspectives and challenges of this concept will be discussed.